Work Discipline and Competency of the Democracy Volunteer of Makassar City in General Election 2019 - Delly Mustafa; Risma Niswaty; Nuzlan Botutihe (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Every organization expects its people resources to perform well in order to accomplish organizational goals. Similarly, expectations for the Makassar City Volunteer Democracy's performance in the 2019 General Election. The relationship between work discipline and the performance of the Makassar City Volunteer Democracy is positive and substantial, as evidenced by the value of Unstandardized Coefficients beta () of 0.262. (26.2 percent ). This suggests that the contribution of work discipline to performance is 26.2 percent. There is a positive and strong relationship between competences and their performance, as evidenced by the value of Unstandardized Coefficients beta () of 0.579. (57.9 percent ). This suggests that the contribution of competence to performance is 56.9 percent. There is an influence of work discipline and competence on their performance concurrently (concurrently). As seen by the R-Square value of 0.574, the extent of the effect of work discipline and competence on performance is that the remaining 57.4 percent is explained or affected by other factors not included in this study.